Meso-level cooperation on transboundary tributaries and infrastructure in the Ferghana Valley - Wegerich, Kai; Kazbekov, Jusipbek S.; Kabilov, F.; Mukhamedova, N. (2012)
The river basin management approach in the Syr Darya basin fragmented after the disintegration of the Soviet Union. However, this approach had already created dependencies between riparian states, such as transboundary water control infrastructure. At the national level, these states hardly cooperate, but at the province and district level, especially in the Ferghana Valley, which is shared by Kyrgyzstan, Tajikistan, and Uzbekistan, cooperation continues. This paper analyzes transboundary cooperation in the Ferghana Valley. On the periphery, conflict and cooperation still take place on both water management infrastructure and water sharing. The greatest hindrance to cooperationborder controlis outside the realm of water management, but is key given the property rights to water management infrastructure in the neighbouring riparian states.